Elevated In Vivo Levels of a Single Transcription Factor Directly Convert Satellite Glia into Oligodendrocyte-like Cells - Weider, Matthias (PLoS Genet, 2015)
Oligodendrocytes are the myelinating glia of the central nervous system and ensure rapid saltatory conduction. Shortage or loss of these cells leads to severe malfunctions as observed in human leukodystrophies and multiple sclerosis, and their replenishment by reprogramming or cell conversion strategies is an important research aim. Using a transgenic approach we increased levels of the transcription factor Sox10 throughout the mouse embryo and thereby prompted Fabp7-positive glial cells in dorsal root ganglia of the peripheral nervous system to convert into cells with oligodendrocyte characteristics including myelin gene expression. These rarely studied and poorly characterized satellite glia did not go through a classic oligodendrocyte precursor cell stage. Instead, Sox10 directly induced key elements of the regulatory network of differentiating oligodendrocytes, including Olig2, Olig1, Nkx2.2 and Myrf. An upstream enhancer mediated the direct induction of the Olig2 gene. Unlike Sox10, Olig2 was not capable of generating oligodendrocyte-like cells in dorsal root ganglia. Our findings provide proof-of-concept that Sox10 can convert conducive cells into oligodendrocyte-like cells in vivo and delineates options for future therapeutic strategies.